Sustainable Sources of Energy and the Expected Benefits to Nigerian Economy - Oluchukwu F, Anowor; Innocent I, Achukwu; Ogochukwu S, Ezekwem (International Journal of Sustainable Energy and Environmental Research, 2014)
Sustainable development entails conservation, preservation, accessibility and affordability. When it comes to energy usage, Nigeria relies mostly on conventional source of energy with quite high opportunity cost making it cost-wise comparatively inaccessible for the poor population. In this work, renewable energy sources like solar radiation which is abundantly present in Nigeria was found to offers a much cheaper alternative in meeting the energy demands since they are derived from natural processes that are replenished constantly. Reviews on the opportunities, government policies and strategic developments of renewable energy in Nigeria were carried out to ascertain its feasibility. From the results, it was possible to highlight how these energy sources can be beneficial in tackling the energy problem in Nigeria.